Pemberdayaan IKM Tenun Unnoni melalui Pelatihan Penentuan Harga Jual Berbasis Biaya Produksi - Mince Batara; Grace Sriati Mengga; Agustinus Mantong; Stefani Marina Palimbong; Olivia Devi Yulian Pompeng; Elisabet Pali (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The Unnoni Weaving Center is a community-led, small and medium-sized enterprise (SME) development center for traditional weaving. Despite its significant potential, many entrepreneurs in this center face challenges in determining appropriate product prices. They typically rely solely on intuition or follow market prices without considering all production cost components, resulting in very small profit margins and even the risk of incurring losses. In response to these challenges, this community service program was designed to improve the ability of SMEs to determine more rational, measurable, and profitable selling prices through comprehensive and applicable training in production cost calculations. The methods employed included outreach, workshops, intensive mentoring, and hands-on simulations on pricing based on real costs and reasonable margins. The program was conducted in two sessions at the Unnoni Weaving Center Hall, involving 25 local weaving entrepreneurs. The results showed significant improvement, with participants' understanding of identifying production cost components increasing by 76%, while approximately 80% successfully conducted simulations for determining selling prices, taking into account raw materials, labor, overhead costs, and profit margins. The tangible impact of this activity is seen in increased business literacy, more systematic calculation skills, and the confidence of SMEs in determining prices and negotiating with consumers and business partners. Furthermore, this activity is expected to be a starting point for the implementation of a simple financial recording system, increased operational efficiency, and the development of a branding strategy for Unnoni woven products so they can compete more professionally, sustainably, and with high competitiveness in both local and global markets.